The Implementation of Compact Development in Moncton, New Brunswick: Perspectives from Developers - Biggar, Jeffrey (Canadian Planning and Policy / Aménagement et politique au Canada)

(untitled) (Association of Canadian University Planning Programs, 2025)
The promotion of compact development aimed at reducing urban sprawl has long been a dominant planning approach in major urban centres. However, mid-sized cities have struggled to cultivate a market for this development model despite policy commitments. This paper examines how property developers in Moncton, New Brunswick, respond to compact development’s principles and policies. Results indicate that while many developers align with the planning policies favouring higher-density and mixed-use models, they prefer suburban development over urban infill and adaptive reuse. Developers generally support compact development but seek greater market certainty and regulatory lessening before fully committing to building greater densities. The research highlights a disconnect between temporal and spatial dimensions of urban development priorities and associated impacts on the implementation of residential densification. While planners focus on spatial aspects to achieve policy goals, developers prioritise the timing of projects to ensure financial feasibility and economically profitable returns.